(untitled) (Journal of Environmental Microbiology and Toxicology, 2025)
Glyphosate remains one of the most extensively applied herbicides worldwide; however, its persistence in the environment raises concerns regarding ecological safety and human health, underscoring the need for sustainable remediation approaches. This study focused on isolating and characterising indigenous soil bacteria from Kota Marudu, Sabah, agricultural soil with the capacity to degrade glyphosate-based herbicides. Soil samples were enriched in minimal salt medium (MSM) supplemented with Roundup for seven days, after which bacterial isolates were screened for tolerance across different Roundup concentrations. Morphological and biochemical profiling was conducted, and partial Identification was achieved using the ABIS online platform. Biodegradation efficiency was evaluated through degradation assays. Three isolates, designated KM1, KM2, and KM4, exhibited tolerance to Roundup concentrations up to 6 mL/L (v/v). Gram staining confirmed all isolates as Gram-positive; KM1 displayed a rod-shaped morphology, whereas KM2 and KM4 were coccoid. Biochemically, KM1 tested positive for catalase activity, all sugar fermentations, the Voges–Proskauer test, and citrate utilisation. KM2 and KM4 were catalase-positive, Voges-Proskauer-positive, and citrate-positive but failed to ferment sucrose while fermenting other tested sugars. ABIS-based Identification suggested KM1 belonged to the genus Bacillus, while KM2 and KM4 were classified as Staphylococcus sp. After three days, glyphosate degradation efficiencies reached 82.8%, 83.1%, and 80.1% for KM1, KM2, and KM4, respectively. These findings highlight the potential of indigenous Gram-positive bacteria in glyphosate biodegradation. Further molecular Identification, optimisation of degradation parameters, and evaluation under field-relevant conditions are warranted to assess their applicability in agricultural bioremediation strategies.